ANALISIS PENGGUNAAN LABEL HALAL TANPA SERTIFIKASI BPJPH PADA PRODUK MAKAN INDUSTRI RUMAHAN DI DESA DASAN TERENG KABUPATEN LOMBOK BARAT PERSPEKTIF HUKUM EKONOMI SYARIAH - Nurhidayani; Fariz Al-Hasni (Universitas Islam Negeri Mataram, 2025)
This study stems from the phenomenon of many businesses in Dasan Tereng Village labeling their products as halal without going through the official certification process. In fact, halal labels can only be used after businesses register their products with the National Halal Product Guarantee Agency (BPJPH) by going through an audit and halal fatwa determination, as stipulated in Law Number 33 of 2014 concerning Halal Product Guarantee. This study aims to examine the factors behind the use of halal labels prior to certification and analyze them from a sharia economic law perspective. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation, as well as data analysis through reduction, presentation, and conclusion drawing. The results of the study indicate that the use of halal labels without certification is influenced by a lack of understanding among business actors, the assumption that the certification process is complicated and time-consuming, and low enthusiasm for halal labeling. In addition, Surah al-Baqarah verse 282 of the Qur'an, which emphasizes the importance of recording as a form of proof, can be used as a normative basis for requiring halal certification.